Transcriptomic response of zebrafish embryos to polyaminoamine (PAMAM) dendrimers. Issue 1 (August 2014) - Oliveira, Eva; Casado, Marta; Faria, Melissa; Soares, Amadeu M. V. M.; Navas, José María; Barata, Carlos; Piña, Benjamin
Abstract The progressive practical applications of engineered nanoparticles results in their ever-increasing release into the environment. Accurate assessment of their environmental and health risks requires the development of methods allowing their monitoring in different environmental compartments and the evaluation of their potential toxicity at different levels of organization. Toxic effects of third-generation (G3) and fourth-generation (G4) poly(amidoamine) dendrimers (ethylenediamine cored, imine-terminated) were assessed on zebrafish embryos during the first two days post-fertilization. Particle characterization by dynamic light scattering showed no tendency to form aggregates in the assay conditions. G3 particles showed somewhat a higher acute toxicity than G4 particles, with LC50 values of 1.8 and 2.3 mg/L, respectively. At sublethal concentrations, both particles affected the zebrafish transcriptome following similar patterns, suggesting a similar mode of action. About 700 transcripts were affected by at least one of the treatments, following a pattern with significant correlations to the effects of bacterial infection in zebrafish embryos. We concluded that the response to G3 and G4 dendrimers was consistent with the activation of the innate immune response, a still unreported potential effect of these particles. These data may contribute to the characterization of hazards of these nanomaterials for both human health and the environment.